RESPON PETANI TERHADAP PENGEMBANGAN TANAMAN SORGUM DI DESA PLEDO KECAMATAN WITIHAMA KABUPATEN FLORES TIMUR - Syarifah Syamsuddin; Leta Rafael Levis; Lika Bernadina (Buletin Ilmiah Impas, 2022)
This study aims to determine: Farmer group members' responses to the development of sorghum. This study uses the survey method. Determination of the research location is done purposively. The population in this study were all members of the farmer group totaling 30 people. To determine the purpose of the data analyzed by descriptive statistical test. The results showed that: The response of farmer group members to sorghum farming is classified as "good" with an average score of 3,69 and the achievement of a maximum score 74%. This means that the development of sorghum in Pledo Village is a new and innovative farming option for land conditions in the research village.